MAINTAINING THE WORK ENVIRONMENT TO IMPROVE EMPLOYEE PERFORMANCE - Rajagukguk, Iswento Rizki Manarissar; Johannes, Johannes; Rosita , Sry (Journal of Business Studies and Management Review, 2025)
The purpose of this research is to determine and analyze the impact of employee skills on the performance of ASN employees through the work environment, using it as a mediating variable in Jambi Province. The population consists of employees who are permitted to pursue higher education, totaling 412 people. Using the Slovin method, the number of samples in this study was calculated to be 81 people. Data analysis was conducted using Partial Least Squares (PLS) techniques, with measurements of the outer model and inner model. The results of the study indicate that employee skill, organizational commitment, and work environment influence employee performance directly, while employee skill and organizational commitment also influence the work environment. Indirectly, it shows that employee skill and organizational commitment influence employee performance through the work environment as a mediating variable.